CRESI: A susceptibility index methodology to assess roads threatened by coastal erosion. (1st November 2021) - Brandes, H.; Doygun, O.; Francis, O.; Zhang, G.; Rossi, C.; Yang, L.; Togia, H.
Abstract: A new method is proposed to assess the susceptibility of coastal roads to structural deterioration from shoreline erosion caused by natural processes such as waves, tides, and the effects of climate change, including sea level rise. The approach is based on a new susceptibility index method called the Coastal Road Erosion Susceptibility Index ( CRESI ) that incorporates key parameters that control road structure and coastal buffer resistance to erosion and impacts from the ocean side. The index was applied to a network of Hawaii State roads and an extensive set of field data and observations were collected throughout all the major islands. This data has been cataloged into a database of coastal road assets that continues to be expanded. Over 300 sites were assessed as part of the project. Based on the value of CRESI, vulnerable road sections were segmented into one of three levels of erosion susceptibility. In addition, the twenty most vulnerable locations were ranked, based largely on the CRESI index, for purposes of road management and planning. Ongoing work relating to improvements in the methodology to better account for traffic and a more accurate set of natural (ocean) processes with a potential hazard risk are also described. The proposed new methodology can be applied to other regions with only minor adjustments for local boundary conditions, if necessary. The results of the applied new method from Hawaiian state roads show that the methodology proves useful and promising for government-, state-, and county-level road authorities and agencies in the assessment of the coastal road erosion problems and their decision making with regard to corresponding remediation measures. Highlights: ∙ A new index method ( CRESI ) is developed and applied to Hawaiian coastal roads to assess their susceptibility to erosion. ∙ Coastal state roads throughout the state were ranked according to the CRESI method to identify the most critical sections. ∙ Site visits of the road sections, which were identified as most susceptible, validated the efficiency of the new method. ∙ The statewide mapping of coastal roads with the CRESI method presents a novel documentation of coastal road erosion in Hawaii. ∙ Although the CRESI method was developed for Hawaii, it can be adapted to other coastal roads with only slight modifications.